Air‐Stable and Volatile Bis(pyridylalkenolato)germanium(II), ‐tin(II), and ‐lead(II) Complexes. Issue 3 (17th December 2013) - Heidemann, Tim; Mathur, Sanjay
Abstract: Homoleptic germanium(II), tin(II), and lead(II) complexes of the general formula M(2‐PyCHCOCF3 )2 (M = Ge, Sn, Pb; Py = pyridine) were synthesized by treating the corresponding silyl amides [M{N(SiMe3 )2 }2 ] with two equivalents of a 3, 3, 3‐trifluoro‐1‐(2‐pyridyl)prop‐1‐en‐2‐ol (2‐PyCHCOHCF3 ) ligand. Single‐crystal X‐ray diffraction revealed the bidentate chelation of 2‐PyCHCOHCF3, which imposes a distorted trigonal bipyramidal geometry for all three molecular structures; this distortion is highest for the lead compound, probably as a result of the high s character of the lone pair of electrons present on the metal centers. The monomeric nature of the compounds in solution was confirmed by multinuclear NMR spectroscopy, whereas a polymeric structure is observed for the lead complex in the solid state. Abstract : Homoleptic germanium(II), tin(II), and lead(II) complexes of the general formula M(2‐PyCHCOCF3 )2 (M = Ge, Sn, Pb; Py = pyridine) with promising properties for chemical vapor deposition applications are synthesized and investigated by multinuclear NMR spectroscopy and single‐crystal X‐ray diffraction.